K voprosu posledovatel'nogo i parallelnogo razvitiya obshchei i spetsial'noi rabotosposobnosti lyzhnikov - Lazarev, G. M.
On technical, dynamic, time related and physiological parameters and data in different intensities (strength - 100%, middle - 80-75%, niedrig - 70-60%) in cross-country skiing and the suitable ways aand intensities of training.